Clinicopathologic Characteristics of 29 Invasive Carcinomas Arising in 178 Pancreatic Mucinous Cystic Neoplasms With Ovarian-type Stroma: Implications for Management and Prognosis. (February 2015) - Jang, Kee-Taek; Park, Sang Mo; Basturk, Olca; Bagci, Pelin; Bandyopadhyay, Sudeshna; Stelow, Edward B.; Walters, Dustin M.; Choi, Dong Wook; Choi, Seoung Ho; Heo, Jin Seok; Sarmiento, Juan M.; Reid, Michelle D.; et al.
Abstract : Information on the clinicopathologic characteristics of invasive carcinomas arising from mucinous cystic neoplasms (MCNs) is limited, because in many early studies they were lumped and analyzed together with noninvasive MCNs. Even more importantly, many of the largest prior studies did not require ovarian-type stroma (OTS) for diagnosis. We analyzed 178 MCNs, all strictly defined by the presence of OTS, 98% of which occurred in perimenopausal women (mean age, 47 y) and arose in the distal pancreas. Twenty-nine (16%) patients had associated invasive carcinoma, and all were female with a mean age of 53. Invasion was far more common in tumors with grossly visible intracystic papillary nodule formation ≥1.0 cm (79.3% vs. 8.7%, P =0.000) as well as in larger tumors (mean cyst size: 9.4 vs. 5.4 cm, P =0.006); only 4/29 (14%) invasive carcinomas occurred in tumors that were <5 cm; however, none were <3 cm. Increased serum CA19-9 level (>37 U/L) was also more common in the invasive tumors (64% vs. 23%, P =0.011). Most invasive carcinomas (79%) were of tubular type, and the remainder (5 cases) were mostly undifferentiated carcinoma (2, with osteoclast-like giant cells), except for 1 with papillary features. Interestingly, there were no colloid carcinomas; 2 patients had nodal metastasis at the time of diagnosis, and both died of disease at 10 and 35 months, respectively. While noninvasive MCNs had an excellent prognosis (100% at 5 y), tumors with invasion often had an aggressive clinical course with 3- and 5-year survival rates of 44% and 26%, respectively ( P =0.000). The pT2 (>2 cm) invasive tumors had a worse prognosis than pT1 (⩽2 cm) tumors ( P =0.000), albeit 3 patients with T1a (<0.5 cm) disease also died of disease. In conclusion, invasive carcinomas are seen in 16% of MCNs and are mostly of tubular (pancreatobiliary) type; colloid carcinoma is not seen in MCNs. Serum CA19-9 is often higher in invasive carcinomas, and invasion is typically seen in OTS-depleted areas with lower progesterone receptor expression. Invasion is not seen in small tumors (<3 cm) and those lacking intracystic papillary (mural) nodules of ≥1 cm, thus making the current branch-duct intraductal papillary mucinous neoplasm management protocols also applicable to MCNs.